s/9+26=29

Simple and best practice solution for s/9+26=29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for s/9+26=29 equation:



s/9+26=29
We move all terms to the left:
s/9+26-(29)=0
We add all the numbers together, and all the variables
s/9-3=0
We multiply all the terms by the denominator
s-3*9=0
We add all the numbers together, and all the variables
s-27=0
We move all terms containing s to the left, all other terms to the right
s=27

See similar equations:

| –11g=18−20g | | N2/5+2n/6=12 | | (5x-15)+(8x-8)=180 | | 16d=14d+18 | | m/7+40=46 | | 186-w=232 | | 6(9+x)=54 | | 9000m=2700 | | 2x2+x+1=0 | | 5s-4s=17 | | 16=b/7+13 | | 7x–10x=9 | | b+13/4=9 | | -(18-4x)=18 | | 17x=-51;x=-3 | | 85=9d+4 | | 9(k+1)=90 | | 5^n=5^11⋅5^3 | | 4x=4x-4+2x | | 5^n=56^11⋅5^3 | | -19+8s=-91 | | 2x+6=×+10 | | -2x4+8x2=0 | | 14x=56;x=6 | | 9x+5x=(-28) | | 20x-40=30x | | -16=8(t-96) | | v-9+15=0 | | 4=p/3-3 | | 7(2a+1)-4(3a+2)=0 | | 71=k/9+66 | | 7x+23=21-11 |

Equations solver categories